Antimicrobial Agent Triclosan Suppresses Mast Cell Signaling via Phospholipase D Inhibition - Shim, Juyoung K. (J Appl Toxicol, 2019)
Humans are exposed to antimicrobial agent triclosan (TCS) through use of TCS-containing products. Exposed tissues contain mast cells, which are involved in numerous biological functions and diseases by secreting various chemical mediators through a process termed degranulation. We previously demonstrated that TCS inhibits both Ca(2+) influx into antigen (Ag)-stimulated mast cells and subsequent degranulation. In order to determine the mechanism linking triclosan’s cytosolic Ca(2+) depression to inhibited degranulation, we investigated TCS effects on crucial signaling enzymes activated downstream of Ca(2+) rise: protein kinase C (PKC; activated by Ca(2+) and reactive oxygen species, ROS) and phospholipase D (PLD). We found that TCS strongly inhibits PLD activity within 15 min post-Ag, a key mechanism of TCS mast cell inhibition. Also, experiments using fluorescent constructs and confocal microscopy indicate that TCS delays Ag-induced translocations of PKCβII, PKCδ, and PKC substrate MARCKS. Surprisingly, TCS does not inhibit PKC activity or overall ability to translocate, and TCS actually increases PKC activity by 45 min post-Ag; these results are explained by the timing of both TCS inhibition of cytosolic Ca(2+) (~15+ min post-Ag) and TCS stimulation of ROS (~45 min post-Ag). These results demonstrate that it is incorrect to assume that all Ca(2+)-dependent processes will be synchronously inhibited when cytosolic Ca(2+) is inhibited by a toxicant or drug. These results offer molecular predictions of triclosan’s effects on other mammalian cell types which share these crucial signal transduction elements and provide biochemical information that may underlie recent epidemiological findings implicating TCS in human health problems.